The hot chocolate effect - Kuk, Rok (Matrika, 2023)
Introducing bubbles into a cup with liquid changes the pitch of the sound it makes when tapped with a spoon. This is known as the hot chocolate effect. Simple experiments that can be performed at home, are presented, demonstrating the changing speed of sound in water when bubbles are present. A simplified but effective mathematical model is derived. In addition to demonstrating the effect, the experiments described provide an opportunity for students to develop skills to think like a scientist by devising and testing explanations.
Keywords: bubbles; frekvenca zvoka; frequency; liquids; mehurčki; sound; tekočine; zvok